2017
DOI: 10.1186/s12936-017-1941-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Plasmodium falciparum specific histidine-rich protein 2 rapid diagnostic test in the context of the presence of non-malaria fevers, prior anti-malarial use and seasonal malaria transmission

Abstract: BackgroundIt remains challenging to distinguish malaria from other fever causing infections, as a positive rapid diagnostic test does not always signify a true active malaria infection. This study was designed to determine the influence of other causes of fever, prior anti-malarial treatment, and a possible seasonality of the performance of a PfHRP2 RDT for the diagnosis of malaria in children under-5 years of age living in a malaria endemic area.MethodsA prospective etiology study was conducted in 2015 among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 24 publications
3
45
1
Order By: Relevance
“…With regards to PPV and NPV, it was observed that RDT exhibited an almost excellent NPV with a meagre PPV. e NPV of the RDT observed by Kiemde et al [25] and Ilombe et al [36] is as good as that in this study, but whilst the PPV in their reports is likewise lower, it is 2-4 folds higher than that in the current study. e results of the current study however do not suggest that the PfHRP2 CareStart ™ RDT is of substandard, but rather re-echo the fact that at very low parasite density (far below the 200 parasites/μL minimum threshold as set by WHO) current batch of RDTs are not very useful and therefore the need for ultrasensitive RDT especially in areas where even microscopy is a challenge and PCR is simply impossible.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…With regards to PPV and NPV, it was observed that RDT exhibited an almost excellent NPV with a meagre PPV. e NPV of the RDT observed by Kiemde et al [25] and Ilombe et al [36] is as good as that in this study, but whilst the PPV in their reports is likewise lower, it is 2-4 folds higher than that in the current study. e results of the current study however do not suggest that the PfHRP2 CareStart ™ RDT is of substandard, but rather re-echo the fact that at very low parasite density (far below the 200 parasites/μL minimum threshold as set by WHO) current batch of RDTs are not very useful and therefore the need for ultrasensitive RDT especially in areas where even microscopy is a challenge and PCR is simply impossible.…”
Section: Discussionsupporting
confidence: 56%
“…Also, these studies and that of Kwenti et al [35], much like this present study, reported RDT to have a rather high specificity than sensitivity. However, contrary to this finding, several other studies have reported higher sensitivity rather than specificity for RDT in asymptomatic individuals [25,[36][37][38]. With regards to PPV and NPV, it was observed that RDT exhibited an almost excellent NPV with a meagre PPV.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In general, the specificity of the HRP2-based RDTs is being questioned particularly under low transmission conditions [20]. This is supported by one of previous studies conducted in the same study area in which a high prevalence of false positive RDT results was reported during the dry season (April–May; low transmission) [22]. However, the present study was mainly conducted during the rainy season (June–October; high transmission season) but still the number of false positive tests was almost twofold higher at the participating health facilities compared to the laboratory of CRUN.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, with the increase in the number of concomitant medication prescriptions, the risk of occurrence of ADRs increased. This could be explained partly by the fact that during the period of high malaria transmission, the diagnosis of malaria episodes (with malaria RDTs) is more accurate 55 and therefore would improve the accuracy in the drug prescription for illness management (less prescription of concomitant therapy). At the same time, the rainy season coincides with the beginning of farming activities, and families usually move from their usual homeland to hamlets with limited geographical accessibility.…”
Section: Discussionmentioning
confidence: 99%